Code-Switching and Emotion in Podcasts: A Paralinguistic and Structural Analysis - Hasnaa Saad Al-Khafaji; Yasir Bdaiwi Jasim Al-Shujairi (WISE Pendidikan Indonesia, 2026)
In an era where digital media redefines how people express themselves, podcasts serve as platforms for emotionally nuanced bilingual interaction. This study examines how Arabic–English speakers in ABtalks, an interview podcast, employ code-switching (CS) and paralinguistic features to convey emotion, identity, and social meaning. Drawing on the typology of CS, paralinguistic framework, and bilingual emotion, four episodes were analyzed using qualitative discourse analysis. Findings reveal that intra-sentential CS dominates (accounting for 92–97% of instances), functioning as an expressive and affective strategy, while inter-sentential and tag-switching occur selectively for emphasis, narrative effect, or authenticity. Paralinguistic cues—including pauses, rising and falling intonation, vocal stress, laughter, and speech rate—consistently align with CS to signal hesitation, emotional intensity, reflection, or psychological regulation. English insertions often universalize or soften emotionally charged content, whereas Arabic anchors intimate, culturally contextualized expressions. The interaction between language choice and vocal delivery demonstrates that speakers deliberately use CS and paralinguistics to perform identity, regulate emotions, and enhance narrative engagement. Future research could examine other podcast genres or bilingual contexts and employ acoustic analysis to explore how prosody and CS jointly shape emotional meaning and digital self-expression.